Responses of Some Cowpea Varieties to Two Striga Stains in Nigeria - L.Y. Amina, S. Muhammad (Journal of Phytology, 2009)
The research was conducted in a greenhouse at the Internatinal Institute of Tropical Agriculture (IITA) to investigate the response of eighteen (18) cowpea varieties to two (2) Striga gesnerioides strain from Samaru of Kaduna Stete and Mingibir in Kano state Guinea and Sudan savannah of Northen Nigeria respectively. A total of 0.5g of the available S. gesnerioides seed from each location was infested in eighteen pots. The dormancy was broken followed by planting of the Cowpea variety. It was observed that the angiospermic parasite response to some Cowpea varieties while some of the Striga was not sensitive to the root exudates. Samarium strains posses high number of Striga emergence but produce high yield. Compared to that of Mingibir. No any response in B301 in both the Samaru’s and Mingibir’s strains.